Is Static Nitrogen Management in Northwestern US Sugarbeet Production Appropriate?. Issue 1 (1st October 2018) - Tarkalson, David D.; Bjorneberg, David L.; Dean, Greg
Abstract : Core Ideas: With increased yields, a yield goal N management approach can lead to oversupply of N. Oversupply of N can increase sugarbeet impurities and decrease profit. N supply needed for max. yield was 179–204 kg N ha −1 for Idaho studies in 1977, 1997, and 2011. Research is needed to evaluate a static N management approach in sugarbeet production. Nitrogen (N) management is important in sugarbeet ( Beta vulgaris L.) production. This paper presents data to support additional research to evaluate a new N management approach in the northwestern United States. Evaluation of historic data suggests that static N management (fixed N supply independent of yields) may have advantages compared with yield goal‐based N management in the northwestern United States. From the early 1970s to 2011, the amount of N supply needed to maximize yields in research studies was within a narrow N supply range of 179 to 204 kg N ha −1 . Recommended N supplies (179–204 kg N ha −1 ) have not increased as yields have increased. Evidence suggests that following the past recommendations under current yield levels will likely oversupply N. On the basis of this analysis, a regionwide project has begun to determine if a static N management approach is appropriate.